Euroland: New conditions for economic policy - Jörg Döpke; Klaus-Jürgen Gern; Jan Gottschalk; Enno Langfeldt; Joachim Scheide; Markus Schlie; Hubert Strauß (Institut für Weltwirtschaft (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1998)
The cyclical situation at the beginning of the European Monetary Union (EMU) is favorable: The upswing in Euroland has firmed, unemployment is going down, and inflation is low. However, economic growth outside the new currency area has weakened significantly during 1998, and fears are mounting that the crises in various regions of the world economy could endanger the current expansion in Euroland. Against this background, the significance of external conditions for the business cycle in Euroland — as well as the regional structure of exports — is analyzed. An important issue for an adequate design of economic policy is to what extent capacities in Euroland are currently utilized and whether cyclical unemployment is still significant. In addition, it is important to know whether the business cycles in the individual countries converge or not. In light of the findings from these analyses, the course of monetary, fiscal, and wage policy is evaluated in order to assess the outlook for Euroland until the end of 1999.
Keywords: 330; Europäische Wirtschafts- und Währungsunion; Wirtschaftspolitik; Konjunktur; Natürliche Arbeitslosigkeit; Konjunkturzusammenhang; Geldpolitik; Finanzpolitik; Lohnpolitik; EU-Staaten